1984
DOI: 10.1111/j.1365-2389.1984.tb00299.x
|View full text |Cite
|
Sign up to set email alerts
|

The association of cobalt with easily reducible manganese in some acidic permanent grassland soils

Abstract: The association of cobalt with manganese oxides was examined in some surface and sub-soils from areas of permanent grassland in England. Hydroquinone (0.2% in ammonium acetate at pH 7.0) was used to extract easily reducible Mn oxides from the soils. Two sequential extractions with this reagent removed significant proportions of the total Co along with the Mn; no significant amounts of iron were extracted. Mn-rich iron concretions were isolated from two of the soils and these contained from 230 to 880 kg g-I Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 25 publications
2
29
0
Order By: Relevance
“…However, it is clear from the present result and those of Jarvis (19846) that the nature of the materials involved, and the overall chemistry of Co in soils, still requires considerable investigation.…”
Section: Relationships Between Extractable and Isotopically Exchangeamentioning
confidence: 67%
“…However, it is clear from the present result and those of Jarvis (19846) that the nature of the materials involved, and the overall chemistry of Co in soils, still requires considerable investigation.…”
Section: Relationships Between Extractable and Isotopically Exchangeamentioning
confidence: 67%
“…Highly significant correlations have been interpreted as the two elements having close associations. Nevertheless, results from such studies have demonstrated that the amounts of Co and Mn extracted in the reducible phase are strongly correlated (Jarvis, 1984), and it has been suggested that the association is due to the strong sorption of Co by Mn oxides. More recently, Li et al (1999Li et al ( , 2001aLi et al ( , 2001b have reported chemical relationships and associations between Co, Mn, and Fe for batch extraction data, based on linear correlation analysis.…”
Section: Evaluation Of Association Between Elements Using Statisticalmentioning
confidence: 98%
“…Co and Mn were shown to be associated to each other in the estuarine sediments. This might be due to the specific adsorption of Co by Mn oxides (Jarvis 1984), and concentrations of Co sorbed by Mn oxides are reported to be much greater than those by Fe oxides (Backes et al 1995). Cr and Ni were also found to be associated to Mn, and this indicated the role of Mn in the scavenging of these metals in the estuarine environment.…”
Section: Metal-granulometric and Inter-metallic Relationshipsmentioning
confidence: 93%